Kesalehan Ayub Dalam Kitab Ayub 2:1-13 Dan Refleksinya Bagi Orang Kristen Masa Kini - Reinhard Florentino Sirait; Hanna Dewi Aritonang; Iwan Setiawan Tarigan (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
The purpose of this research is to find out the meaning of Job's piety amidst suffering in the context of Job 2:1-13 and to reflect on Job's piety amidst the suffering of Christians today. The research method used in this research explores the themes of piety and perseverance in the context of Job 2:1-13 through an exegetical study approach. Job, a figure in the Bible who experienced severe suffering and trials, is the center of attention in this writing. This study considers the picture of Job's piety, despite facing extraordinary trials, still persevering in piety and maintaining his faith. From the context of the book of Job and his life experiences, a picture of the meaning of a believer being able to face suffering is drawn. This suffering is an inseparable part of the reality of human life. More than that, the suffering experienced by believers can be considered a gift from Allah which aims to bring their personal relationship with Him closer. The main key in facing suffering is to carry it out with strong piety, because this strengthens the human bond with Allah. Even though Job experienced tremendous suffering, Job never turned his back on God; on the contrary, Job remained faithful to Him. Job's story should be an example for believers today, remembering that in every hardship, struggle and suffering, steadfast faith and piety should encourage Christians to continue to draw closer to God.